F.L. de Castelnau’s collection of fishes from the Cape of Good Hope described by Pieter Bleeker - Russell, Barry C; van Oijen, Martien J P (Zootaxa, 2021)
The Dutch ichthyologist Pieter Bleeker described 34 species, including a new genus and five new species from a collection of fishes sent to him from the Cape of Good Hope by the French explorer, naturalist and diplomat, F.L. de Castelnau in 1858. A careful search of the Naturalis collection in Leiden found almost all the specimens received by Bleeker from Castelnau, including hitherto unrecognised types. Based on examination of this collection and a critical translation of Bleeker’s 1859 paper on the fishes of the Cape of Good Hope it has been possible to resolve the taxonomic status of Bleeker’s genus Pagrichthys (Pagrichthys castelnaui Bleeker, 1859, type by monotypy), previously considered a synonym of Sparus Linnaeus, 1758 but here regarded as a synonym of Lithognathus Swainson, 1839. The identity of the various species described by Bleeker, and type status of his new species are clarified: Cantharus castelnaui Bleeker, 1859 is a synonym of Pachymetopon blochii (Valenciennes, 1830); Pagrichthys castelnaui Bleeker, 1859 is a synonym of Lithognathus lithognathus (Cuvier, 1829); Seriola capensis Bleeker, 1859 (not previously recognised as a valid species) is a synonym of Seriola lalandi Valenciennes, 1833; Clinus dubuis Bleeker, 1859 (based on a misspelling of Castelnau’s ms name dubius) is a valid name, and a synonym of Clinus superciliosus (Linnaeus, 1758); and Clinus dorsalis Bleeker, 1859 is valid as Muraenoclinus dorsalis (Bleeker, 1859).